2016
DOI: 10.1021/jacs.6b03134
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Composition Tunable and Highly Luminescent Cesium Lead Halide Nanowires through Anion-Exchange Reactions

Abstract: Here, we demonstrate the successful synthesis of brightly emitting colloidal cesium lead halide (CsPbX3, X = Cl, Br, I) nanowires (NWs) with uniform diameters and tunable compositions. By using highly monodisperse CsPbBr3 NWs as templates, the NW composition can be independently controlled through anion-exchange reactions. CsPbX3 alloy NWs with a wide range of alloy compositions can be achieved with well-preserved morphology and crystal structure. The NWs are highly luminescent with photoluminescence quantum y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
404
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 419 publications
(437 citation statements)
references
References 27 publications
(26 reference statements)
18
404
1
1
Order By: Relevance
“…[6,43,27,[86][87][88] In light of this, there are also a few reported works that utilize the solution processable method to synthesize lead halide perovskite nanorods (NRs) and NWs. [37,80,83,89,90] Yang et al were the first to synthesis vertical CH 3 NH 3 PbBr 3 NR arrays by spin-coating a saturated methanolic solution of lead acetate onto substrates, which were then immersed in a CH 3 NH 3 Br solution. [86] Their study revealed the possibility of large-scale production of perovskite NR arrays for various potential optoelectronic applications.…”
Section: D Perovskite: Nanowires and Nanorodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,43,27,[86][87][88] In light of this, there are also a few reported works that utilize the solution processable method to synthesize lead halide perovskite nanorods (NRs) and NWs. [37,80,83,89,90] Yang et al were the first to synthesis vertical CH 3 NH 3 PbBr 3 NR arrays by spin-coating a saturated methanolic solution of lead acetate onto substrates, which were then immersed in a CH 3 NH 3 Br solution. [86] Their study revealed the possibility of large-scale production of perovskite NR arrays for various potential optoelectronic applications.…”
Section: D Perovskite: Nanowires and Nanorodsmentioning
confidence: 99%
“…Zhang et al reported that the CsPbX 3 perovskite NW yield was remarkably enhanced by substituting the OLA with octylamine. [90] Additionally, CsPbBr 3 perovskite NWs can be transformed into CsPbCl 3 and CsPbI 3 perovskite NWs by reacting them with other halide precursors; such reactions are known as anion exchange reactions, which demonstrated high quantum efficiencies of 83% and 30% for CsPbI 3 and CsPbCl 3 perovskite NWs, respectively. The anion exchange reactions maintained the single-crystalline features of CsPbI 3 and CsPbCl 3 , as indicated by high-resolution transmission electron microscope (HRTEM) images.…”
Section: D Perovskite: Nanowires and Nanorodsmentioning
confidence: 99%
“…Interestingly, it has been shown that these materials, both in bulk and in nanocrystalline form, can undergo fast anion-exchange reactions at the solid-liquid or solid-gas interface, with a fine-tuning of the chemical composition and electronic properties (11)(12)(13)(14). The fast ion-exchange kinetics in halide perovskite are related to the low defect formation energy and the existence of a large number of vacancies, which make the ions highly mobile in the crystal lattice (15). As a result, the anionexchange reaction in halide perovskites favors forming homogeneous alloys instead of any kind of heterostructures as commonly observed in II-VI semiconductor compounds.…”
mentioning
confidence: 99%
“…The NWs of Cs-LHQDs with tunable compositions can be halide exchanged using OLAM/OLA at 80°C. 88 The important point is that these Cs-LHQDs can effectively function as "halide reservoirs" to exchange the halide ions with organohalides in solution. 29 Because of the large difference in the ionic radii, the exchange of the I − to Cl − occurs through an intermediate solid-solution formation, whereas all other halide exchange processes happen through solid-solution formation (i.e., mixture of Cl/Br, Br/I, Br/Cl, I/Br state).…”
Section: Halide Exchange In Cs-lhqdsmentioning
confidence: 99%
“…Interestingly, it was observed that replacing OLA by OTA lead to the formation of Cs-LHQDs nanowires (NWs). 52 Moreover, the addition of short-chain ligands such as octanoic (or) nonanoic acid and OCT into the above reaction mixture (Cs-oleate) leads to the formation of orthorhombic CsPbBr 3 NSs with a thickness of ∼3 nm and lateral dimensions 300 nm to a few micrometers; the lateral size can be tuned by varying the different ratios of addition of these ligands. 53 Also, the different chain lengths of carboxylic acid and alkylamine used in the reaction would also influence the final morphology of the QDs.…”
Section: Introductionmentioning
confidence: 99%